(untitled) (Islas, 2026)
Introduction: The cemetery underwent a process of renewal during the nineteenth century, manifested in the succession of three fundamental models: the parish-emergent, the enlightened-intermediate, and the romantic-evolved. The main objective of this study is to analyze the contributions of each model to the conception and materialization of the ideal cemetery. The romantic-evolved model is proposed as the one closest to the ideal cemetery. This proposal is grounded in its capacity to overcome the limitations of its predecessors, allowing it to remain in use today as a valid alternative. Methods: Both theoretical and empirical methods are employed. The historical method is applied to examine the development of the cemetery as a project over time in diverse yet analogous contexts. The induction–deduction–induction method makes it possible to formulate theories based on existing theory. Direct observation is used, together with the consultation and systematization of primary and secondary sources on cemeteries in Europe and Latin America. Results: The study analyzes the principal contributions of the romantic-evolved model, with emphasis on its functioning, location, artistic design, incorporation of scientific principles, landscape value, adoption of a regulatory framework, and the process of chapel individualization. Conclusions: The study demonstrates the extent to which the romantic cemetery approximated the ideal sought during the nineteenth century and confirms its continued validity in relation to the needs of the contemporary city.